Renovation of shaft mining building no. 2 in Kłodawa Salt Mine = Renowacja budynku nadszybia nr 2 na terenie Kopalni Soli "Kłodawa" s.a. - Błaszczyński, Tomasz; Wielentejczyk, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the renovation process of the shaft mining building No. 2 situated in the Kłodawa Salt Mine. A technical state of the facility required immediate reinforcement of structural elements, which was confirmed by expertise carried out by the authors. A lack of repairs could be the cause of building damage. The progress of corrosion in some steel profiles of columns or floors was very advanced.
Keywords: konstrukcje stalowe; wzmacnianie konstrukcji; renowacja; modernizacja; korozja; trwałość konstrukcji stalowych; strengthening of steel structures; renovation; modernization; durability of steel structures; corrosion